Neutrophil-to-Lymphocyte Ratio Predicts Prognosis in Castration-Resistant Prostate Cancer Patients Who Received Cabazitaxel Chemotherapy. (29th August 2017) - Uemura, Koichi; Kawahara, Takashi; Yamashita, Daisuke; Jikuya, Ryosuke; Abe, Koichi; Tatenuma, Tomoyuki; Yokomizo, Yumiko; Izumi, Koji; Teranishi, Jun-ichi; Makiyama, Kazuhide; Yumura, Yasushi; Kishida, Takeshi; et al.
Abstract : Introduction and Objectives . An elevated neutrophil-to-lymphocyte ratio (NLR) has been suggested to be associated with a poor prognosis in several cancers. We evaluated the utility of an elevated NLR as a biomarker to predict the prognosis of metastatic castration-resistant prostate cancer (mCRPC) patients treated with cabazitaxel (CBZ). Methods . We analyzed 47 patients who received CBZ chemotherapy for mCRPC in our institutions. The NLR was calculated using the neutrophil and lymphocyte counts before CBZ chemotherapy. We determined the NLR cut-off value based on the sensitivity and specificity levels derived from area under the receiver operator characteristic curves for death. A multivariate analysis was performed to investigate the association between the NLR and the prognosis. Results . The median overall survival (OS) after CBZ was 10.0 months (range: 6.3–13.2). The median OS was shorter in patients with a high NLR (≥3.83) than in those with a low NLR (<3.83) (5.8 versus 13.2 months, p = 0.018 ). In the multivariate analysis, the NLR, patient age, and lymph node (LN) metastasis were independent predictors of the OS (hazard ratio 3.01, p = 0.030 ; hazard ratio 3.10, p = 0.029 ; hazard ratio 12.38, p = 0.001, resp.). Conclusions . NLR might be a useful prognostic biomarker in mCRPC patients treated with CBZ.